PENGARUH LEADER MEMBER EXCHANGE DAN EMPLOYEE ENGAGEMENT TERHADAP ORGANIZATIONAL CITIZENSHIPSHIP BEHAVIOR (OCB) DENGAN MEDIASI KEPUASAN KERJA - Mulyadi, 1342020049 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the Influence of Leader Member Exchange and Organizational Citizenshipship Behavior Mediated Performance Against Job Satisfaction. In this study, the population of all employees of the Department of Health at the health center employees Tersono, Gringsing I and Limpung. Medium samples were collected based kuseioner many as 134 people who entered as a respondent to the census method. Measurements using a Likert scale of 7 (seven) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Leader Member Exchange positive and significant impact on job satisfaction, (ii) employ Engagement positive and significant impact on job satisfaction, (iii) Leader Member Exchange is not positive and significant impact on Organizational Citizenship Behavior , (iv) employ Engagement is not positive and significant impact on Organizational Citizenship Behavior, (v) Job Satisfaction positive and significant impact on Organizational Citizenship Behavior, (vi) Job Satisfaction mediates the influence of Leader Member Exchange on Organizational Citizenship Behavior, and (vii) Satisfaction Work mediate the effect employ Citizenship Engagement on Organizational Behavior. Keywords: Leader Member Exchange, Employee Engagement, Job Satisfaction, and Organizational Behavior Citizenship.